Juncus dichotomus Elliott (Juncaceae), a new alien species for the flora of Ukraine - Olshanskyi, I.G.; Orlov, O.O. (Український ботанічний журнал, 2013)
Juncus dichotomus is reported for the Ukrainian flora. This is an alien species of North American origin. Now in Ukraine Juncus dichotomus is known in Zhytomyr Region and Volyn Region. Diagnostic features and data on distribution of this species are presented.